Pretty Woman Walking Down the Street - Gade, Solveig (Peripeti, 2023)
Pretty Woman Walking Down the Street. Interview with Biering and Kristensen by Gade. The interview explores the artistic strategy around the performance Pretty Woman A/S (2008), performed by female prostitutes, which triggered a strong public debate.